Construction of a reference material panel for detecting KRAS/NRAS/EGFR/BRAF/MET mutations in plasma ctDNA. Issue 5 (17th August 2020) - Xu, Jun; Qu, Shoufang; Sun, Nan; Zhang, Wenxin; Zhang, Juanli; Song, Qingtao; Lin, Mufei; Gao, Wei; Zheng, Qiaosong; Han, Mipeng; Na, Chenglong; Xu, Ren; et al.
Abstract : Background: The absence of high-quality next-generation sequencing (NGS) reference material (RM) has impeded the clinical use of liquid biopsies with plasma cell-free DNA (cfDNA) in China. Objective: This study aimed to develop a national RM panel for external quality assessment and performance evaluation during kit registration of non-small-cell lung cancer (NSCLC)-related Kirsten rat sarcoma viral oncogene ( KRAS )/neuroblastoma ras oncogene ( NRAS )/epidermal growth factor receptor ( EGFR )/B-type Raf kinase ( BRAF )/mesenchymal–epithelial transition factor ( MET ) genetic assays using plasma circulating tumor DNA (ctDNA). Methods: Mutation cell lines detected by NGS and validated by Sanger sequencing were selected to establish the RM. Cell line genomic DNA was sheared and used to spike basal plasma cfDNA at 10% concentration. Then, the calibration accuracy was determined by four sequencing platforms. Average values were adopted and diluted to 0.1%, 0.3%, 1% and 3% concentrations with basal plasma as the RM panel. Then, five manufacturers were invited to evaluate the performance of the RM panel. Results: 20 cell lines with 23 clinically important mutations were selected, including six mutations in KRAS, two mutations in NRAS, three in BRAF, four in phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha ( PIK3CA ), six in EGFR, one EGFR Gain (4-5 copy) and one MET Gain (2-5 copy). The RM panel consisted of 87 samples, including these 21 mutations at four concentrations (0.1%, 0.3%, 1% and 3%), one MET gain, one EGFR gain and one wild type. The detection rate was 100% for the 3%, 1% and 0.3% samples at all five companies. For the 0.1% concentration, 15 samples had inconsistent results, but at least three companies had correct results for each mutation. Conclusion: RM for a KRAS / NRAS / EGFR / BRAF / MET mutation panel for plasma ctDNA was developed, which will be essential for quality control of the performance of independent laboratories.